The Potential Utility for Massage Therapy During Pregnancy to Decrease Stress and Tobacco Use - O’Hair, BA, Cayla M.; Armstrong, MA, LMT, Kathryn; Rutherford, PhD, Helena J.V. (International Journal of Therapeutic Massage & Bodywork, 2018)
Background: A significant number of women continue to smoke tobacco during pregnancy despite the increased risk of complications to fetal and infant development. Therefore, effective interventions are needed to assist pregnant women with the process of tobacco cessation. Traditional counseling programs have demonstrated some success; however, novel approaches that target stress as a mechanism in the maintenance of addiction would be valuable. Objective: To examine the role of stress in addiction and the utility of massage therapy to decrease stress during pregnancy. Conclusion: Preliminary evidence suggests massage therapy may be beneficial to decreasing tobacco use, and research in pregnant populations is needed.